The Effect of Peer Feedback on Students’ English Speaking Ability - Wahyuddin Wahyuddin; Agus Setiawan (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2026)
This study investigates the effect of peer feedback on students’ English speaking ability among eleventh-grade EFL learners. The research aims to determine whether peer feedback significantly improves students’ speaking performance in terms of fluency, accuracy, pronunciation, vocabulary, and comprehension. The study employed a quantitative pre-experimental design using a one-group pre-test and post-test approach. The participants consisted of 30 eleventh-grade students at a senior high school. Data were collected through speaking tests, observation sheets, and scoring rubrics adapted from Brown and Abeywickrama (2010). The findings revealed a significant improvement in students’ speaking performance after the implementation of peer feedback activities. The mean score increased from 61.4 in the pre-test to 78.2 in the post-test. A paired-sample t-test showed a statistically significant difference between pre-test and post-test scores (t(29) = 9.87, p < .001). Furthermore, Cohen’s d analysis indicated a large effect size (d = 1.21), demonstrating the substantial impact of peer feedback on students’ speaking ability. Classroom observations also revealed increased confidence, participation, interaction, and motivation among students. The study concludes that peer feedback is an effective collaborative learning strategy for improving EFL students’ speaking ability. Therefore, English teachers are encouraged to integrate peer feedback into speaking classrooms to enhance students’ communicative competence.